Pengaruh Kinerja Penyaluran Bantuan Pemerintah Terhadap Masyarakat Putus Sekolah Berbasis Sistem Informasi Manajemen E-Proposal Banper, Transformasi Organisasi dan Kapabilitas SDM pada Lembaga Kursus - Eva Komalasari; Mombang Sihite; Edy Supriyadi (Journal of Management and Leadership, 2021)
The purpose of this study was to evaluate the performance of the distribution of government assistance to dropout communities based on the e-proposal management information system, organizational transformation, and human resource capabilities of course institutions. The sampling technique was purposive sampling—data collection using questionnaires and FGD. The data analysis technique used Structural Equation Modeling (SEM) analysis processed with Smart PLS software. The research results prove that organizational transformation does not directly affect organizational performance in the distribution of government assistance. Meanwhile, HR capabilities and management information systems of e-proposal Banper directly affect organizational performance in the distribution of government assistance. Then organizational transformation indirectly has a significant effect on organizational performance in distributing government assistance by mediating the management information system e-proposal Banper. Likewise, human resource capability indirectly has a significant effect on organizational performance in distributing government assistance by mediating the management information system e-proposal Banper. The results of the strategy analysis through the input strategy stage with CPM, matching stage with TOWS, and decision stage with QSPM, concluded that the strategy used from the QSPM results is a strategy for developing SIM e-proposal assistance.